Enhancing Immunization Education for Future Pharmacists ‎Amid The Evolving Global Community Pharmacy Landscape - Sachdeva, Monika; Aburahma, Mona; Kamil, Noon Abubakr Abdelrahman; Wong, Pei Nee (International Journal of Basic and Applied Sciences, 2025)
In the past decade, the role of community pharmacists has significantly expanded, particularly in developed countries, to support public ‎immunization due to their accessibility and widespread availability. Pharmacists are now actively involved in vaccination recommendation, ‎counseling, and administration, having previously only been involved in vaccine procurement, storage, and dispensing. This change, backed ‎by favorable public health results, has led legislators throughout the world to let pharmacists participate in vaccination campaigns. ‎Pharmacists in some community pharmacies in Abu Dhabi and Dubai have begun giving COVID-19 and flu shots in the United Arab ‎Emirates since August 2022. It is anticipated that this move will improve accessibility and vaccination coverage rates, and future regulatory ‎developments will probably include a wider variety of vaccinations in community pharmacies. This research aims to assess pharmacy ‎students’ attitudes, immunization knowledge, and preparedness for vaccination tasks to identify potential curriculum gaps along with ‎educational interventions required for their expanding responsibilities. A structured, anonymous survey was made with Google Forms and ‎distributed via email to third-, fourth-, and fifth-year pharmacy students. The questionnaire’s five primary themes were demographic data, ‎vaccination knowledge, attitudes and beliefs, preparedness for vaccine-related skills, and recommendations for education. Vaccine ‎knowledge was assessed using a scoring method, whereas attitudes, preparedness, and educational needs were assessed using a five-point ‎Likert scale. The questionnaire underwent a pilot study and expert validation before full implementation. The information was gathered in ‎March 2023 and analyzed using SPSS (version 23.0). The training of pharmacists must change to keep up with the ongoing worldwide ‎evolution of pharmacy practice. Most students (94.9%) believed pharmacist-administered vaccines improve access, and 87.1% supported ‎their role. While confidence in vaccine counseling (84.6%) and public health participation (84.5%) was high, only 61% felt prepared to ‎explain vaccine mechanisms. This research will help identify current educational gaps and inform necessary curriculum modifications to ‎better equip future pharmacists for immunization services. By integrating vaccine administration training into pharmacy education, students ‎can develop the necessary skills and confidence to effectively promote, counsel, and administer vaccines in their communities.